2018
DOI: 10.11648/j.nano.20180601.11
|View full text |Cite
|
Sign up to set email alerts
|

Different Methods Used for the Synthesis of TiO2 Based Nanomaterials: A Review

Abstract: Titanium dioxide is a widely accepted photocatalyst due to its high oxidation efficiency, non-toxicity, high photostability, chemical inertness and environmentally friendly nature. There are several number of attempt have been made to synthesize TiO 2 nanomaterials with different methods. In this paper we have to show the effect of synthesis methods and their surface morphology with temperature. The different methods are used for the synthesis of different Titania based nanomaterials. These methods are sol-gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 41 publications
0
28
0
4
Order By: Relevance
“…The methods can roughly be divided into thermal reactions, deposition methods, sol–gel, Micelle, and electromagnetic methods. In general, the thermal methods are heterogeneous reactions in the presence of aqueous solvents or mineralizers under high pressure and temperature [ 78 , 79 , 80 ]. Deposition methods (e.g., chemical vapor deposition and electrodeposition) are primarily used to create thin-film materials or coatings on a substrate [ 81 , 82 , 83 ].…”
Section: Solar-driven Hydrogen Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods can roughly be divided into thermal reactions, deposition methods, sol–gel, Micelle, and electromagnetic methods. In general, the thermal methods are heterogeneous reactions in the presence of aqueous solvents or mineralizers under high pressure and temperature [ 78 , 79 , 80 ]. Deposition methods (e.g., chemical vapor deposition and electrodeposition) are primarily used to create thin-film materials or coatings on a substrate [ 81 , 82 , 83 ].…”
Section: Solar-driven Hydrogen Productionmentioning
confidence: 99%
“…Deposition methods (e.g., chemical vapor deposition and electrodeposition) are primarily used to create thin-film materials or coatings on a substrate [ 81 , 82 , 83 ]. Sol–gel methods utilize the conversion of a liquid solution (sol) into a solid gel phase, in which the nanoparticles are formed by hydrolysis and condensation [ 78 , 84 ]. Micelles are the long-chain molecules made by surfactants, which contain a hydrophilic head and a hydrophobic chain.…”
Section: Solar-driven Hydrogen Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of aqueous solution or mineralizers under high pressure and low temperature encourages interaction of precursor materials during the process. This method has the feature to make high crystalline nanostructures or products at relatively low temperature [13,14]. A range of TMCs that include NiS [15], CuS, FeS 2 , NiS 2 [10], etc.…”
Section: Different Preparation Methodsmentioning
confidence: 99%
“…In recent years, researchers have done a lot of research and have found that the photocatalytic efficiency can be improved by inhibiting the combination of photogenerated electrons and holes [7]. In order to improve the photocatalytic performance of TiO 2 , many methods have been used to modify it, including metal ion and non‐metal ion doping [8, 9], heat treatment [10] and surface modification [11]. Among them, metal ion doping is the most effective way to improve the photocatalytic performance of TiO 2 and broaden its spectral response range.…”
Section: Introductionmentioning
confidence: 99%